2021
DOI: 10.1038/s41598-021-84497-y
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota resilience in horse athletes following holidays out to pasture

Abstract: Elite horse athletes that live in individual boxes and train and compete for hours experience long-term physical and mental stress that compromises animal welfare and alters the gut microbiota. We therefore assessed if a temporary period out to pasture with conspecifics could improve animal welfare and in turn, favorably affect intestinal microbiota composition. A total of 27 athletes were monitored before and after a period of 1.5 months out to pasture, and their fecal microbiota and behavior profiles were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 73 publications
4
26
0
Order By: Relevance
“…This likely holds true for the respiratory microbiota. Our previous findings in the gut (Mach et al, 2020;Mach et al, 2021a;Mach et al, 2021b) also highlight the possibility that the airway microbiota may be particularly sensitive to where a horse lives and what a horse does. In fact, short-term changes in housing and forage type alters the pulmonary microbiota in horses (Fillion-Bertrand et al, 2019), as well as the contact with animals and people who work at horse facilities, veterinary health care and medication (Kauter et al, 2019).…”
Section: Environmental Stressors As Drivers Of the Respiratory Microbiota Composition And Dynamics Across Speciesmentioning
confidence: 75%
See 1 more Smart Citation
“…This likely holds true for the respiratory microbiota. Our previous findings in the gut (Mach et al, 2020;Mach et al, 2021a;Mach et al, 2021b) also highlight the possibility that the airway microbiota may be particularly sensitive to where a horse lives and what a horse does. In fact, short-term changes in housing and forage type alters the pulmonary microbiota in horses (Fillion-Bertrand et al, 2019), as well as the contact with animals and people who work at horse facilities, veterinary health care and medication (Kauter et al, 2019).…”
Section: Environmental Stressors As Drivers Of the Respiratory Microbiota Composition And Dynamics Across Speciesmentioning
confidence: 75%
“…The gut of ruminants (Ramayo-Caldas et al, 2019), pigs (Mach et al, 2015;Ramayo-Caldas et al, 2016), horses (Mach et al, 2020;Mach et al, 2021a), companion animals (Alessandri et al, 2020) and chickens (Rychlik, 2020) accommodates a complex community of microorganisms that live in a commensal relationship with their hosts and provide significant contributions to the metabolism and immune responses. It might be hypothesized that in symbiosis, gut microbiota ensures the uptake of microbial metabolites that favorably affects the immune and endocrine pathways involved in respiratory disease and progression, whereas the lungs maintain inflammatory homeostasis in the gut by controlling immune response.…”
Section: The Gut-lung Axis During Respiratory Diseases: Key To Understanding Holobiont Functioningmentioning
confidence: 99%
“…Detailed description of the DNA isolation process, V3-V4 16S rRNA gene sequencing-PCR amplification is presented by our group 11,12,17,57,63,65,66 .…”
Section: Methodsmentioning
confidence: 99%
“…New evidence has shown that the gut microbiome and its associated metabolites impact host athletic performance during endurance racing in humans 6,7 . The gut microbiome produces thousands of unique small molecules that can potentially affect many aspects of physiology such as regulating immunity, hydration and redox reactions as well as shaping the gut-brain axis that affects fatigue and stress perception 2, [8][9][10][11][12] . These metabolites can act locally in the intestine or can accumulate up to millimolar concentrations in different body fluids 13 .…”
mentioning
confidence: 99%
“…Brain analyses via electroencephalograms, assessment of intestinal microbiota composition, and behavior measurements revealed a positive influence of keeping horses at pasture on the physical and mental wellbeing, as opposed to single housing systems without pasture access [7,46]. These results seen in horses kept in confinement suggest that welfare may be compromised when horses are not provided with access to pasture.…”
Section: Turnout As a Welfare Concernmentioning
confidence: 99%